Arctic archaeological sites threatened by climate change: A regional multi‐threat assessment of sites in south‐west Greenland. (7th August 2020) - Fenger‐Nielsen, R.; Elberling, B.; Kroon, A.; Westergaard‐Nielsen, A.; Matthiesen, H.; Harmsen, H.; Madsen, C. K.; Stendel, M.; Hollesen, J.
Abstract : Climate change threatens many well‐preserved archaeological sites in the Arctic. The paper presents the first Arctic multi‐threat assessment focusing on the Nuuk region of Greenland. The results suggest that the majority of the 336 known archaeological sites are already exposed to impacts from microbial degradation, permafrost thaw and vegetation, and that these impacts will increase over the next 80 years. Additional impacts from coastal erosion are only noted at a limited number of sites due to a predominant consolidated and uplifting coast. The applied methods represent an important first step to identify threatened sites and emphasize important data limitations.